Regenerated PE plastic and preparation method thereof
Through the grading treatment of recycled PE plastics and the embedding of modified nanographene oxides, combined with the use of thermoplastic elastomers and phthalate coupling agents, the problem of insufficient aging resistance of recycled PE plastic insulation materials has been solved, and the aging resistance of recycled PE plastics has been significantly improved. The material's aging resistance and thermal insulation properties.
Patent Information
- Application Number
- CN202411335784.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When recycled PE plastic is used in thermal insulation materials, its aging resistance is insufficient, resulting in rapid attenuation of thermal insulation performance and affecting the service life of the product.
By grading the recovered PE plastic, adding modified nanographene oxide and thermoplastic elastomer, low-speed shear mixing and extrusion granulation, combining the embedding and ultrasonic treatment of phthalate coupling agent, PE polymers are regulated by regulating the PE polymer after being controlled by adding modified nanograph graphene oxide and thermoplastic elastomer. The crystallization behavior of the chain enhances the material's aging resistance.
It significantly improves the aging resistance of recycled PE plastics, extends the service life of heat insulation materials, and effectively avoids the penetration and corrosion of oxygen and moisture.
Smart Images

Figure BDA0005058195990000071
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer materials and more specifically relates to a recycled PE plastic and a preparation method thereof. Background Art
[0002] As the consumption of polyethylene (PE) continues to increase, the amount of waste PE is gradually increasing. Common methods for dealing with waste PE include incineration and landfill. Incineration can easily cause secondary environmental pollution to the atmosphere, and landfill leads to soil pollution. By recycling waste PE for reuse, environmental pollution can be solved and energy consumption can be saved. The recycling methods of waste PE include mechanical recycling and chemical recycling. In mechanical recycling, the sorting method, melt reprocessing and pollution-free clean technology of PE are the key points. Due to the wide range of sources and large differences in quality of recycled PE, the performance stability of recycled PE may be poor. Chemical recycling of waste PE can realize the resource utilization of carbon-containing solid waste. However, in actual operation, the operating cost of chemical recycling is high and the technology is not yet mature. Direct degradation of waste PE may lose its original performance.
[0003] One of the application approaches is to regenerate discarded PE plastics by adopting appropriate recycling methods and use them as thermal insulation materials. However, the inventors have found that due to the combined influence of the type of raw materials and the process methods in the regeneration process, the recycled plastics are prone to insufficient aging resistance when used as thermal insulation materials, resulting in a very limited service life of the thermal insulation materials, thereby limiting the wide application of the product. Summary of the invention
[0004] The technical problem to be solved by the present invention is: for recycled PE plastic, when it is used as a thermal insulation material, it is faced with the problem that the material is easily aged rapidly due to being in a hot environment for a long time, and the thermal insulation performance is rapidly decayed, which affects the service life of the product. The present invention provides a recycled PE plastic and a preparation method thereof.
[0005] The purpose of the present invention is to provide a method for preparing recycled PE plastic.
[0006] Another object of the present invention is to provide a recycled PE plastic.
[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0008] A method for preparing recycled PE plastic, the specific preparation steps comprising:
[0009] The recycled PE plastics are graded and first-class high-quality PE plastics are selected;
[0010] The first-grade high-quality PE plastic is washed with water, and then dried to remove moisture to obtain a pretreated first-grade high-quality PE plastic;
[0011] The pretreated first-grade high-quality PE plastic, modified nano-graphene oxide and thermoplastic elastomer are heated to 160-165° C. in a mass ratio of (95-100): (6-8): (10-12), and are kept warm and low-speed shear mixed for 8-12 hours under an inert gas protection state, and then extruded and granulated, and cooled to obtain recycled PE plastic;
[0012] Phthalate coupling agents are embedded between the layers of the modified nano-graphene oxide.
[0013] Firstly, the above technical solution uses first-grade high-quality PE plastic as recycled raw material, so as to minimize the introduction of unknown impurities in other second-grade, third-grade, and even fourth-grade classified plastics, so as to avoid the introduction of impurities affecting the application of products in thermal insulation materials;
[0014] Secondly, the above technical solution adds corresponding mass of modified nano-graphene oxide and thermoplastic elastomer in the material regeneration process. In the process of low-speed shear mixing, the layered structure of modified nano-graphene oxide with phthalate coupling agent embedded in the interlayer will gradually peel off under the action of shear force and the viscosity of the system. The phthalate coupling agent adsorbed on its surface can interact with the polymer chain of PE plastic, and the edge of the layered structure of the single layer after peeling is easy to pull each other with the polymer chain of PE plastic, which is beneficial to the stretching of its molecular chain, thereby facilitating the stretching of PE. The polymer chains and the molecular chains of the thermoplastic elastomer form a full and uniform blend, so that the crystallization behavior of the PE polymer can be regulated, thereby reducing the molecular chain damage of the PE plastic molecules during the regeneration process, and can reduce the probability of molecular chain breakage under the conditions of high temperature and oxygen during use, so that the aging resistance of the product is improved; in particular, through the above-mentioned action, the single-layer structure of graphene oxide can be peeled off and freely dispersed inside, thereby effectively avoiding the diffusion and penetration of oxygen, moisture, etc. into the interior, and playing a good shielding role against aging and corrosive media.
[0015] Further, the heat preservation low speed shear mixing comprises:
[0016] Low speed shear mixing is performed at a shear rate of 80-120 r / min.
[0017] Furthermore, the first-grade high-quality PE plastic is selected from beverage bottles made of PE material.
[0018] Furthermore, the specific modification steps of the modified nano graphene oxide include:
[0019] After mixing nano graphene oxide and water, ultrasonically disperse them for 40-60 minutes under an ultrasonic frequency of 180-200kHz, adjust the pH to 7.4-7.6, add 6-8% of the mass of the nano graphene oxide phthalate coupling agent, heat and stir to react, filter, wash and dry to obtain modified nano graphene oxide.
[0020] Ultrasonic treatment is performed at a relatively high ultrasonic frequency, thereby allowing the lamellar structure of graphene oxide to be peeled off, so that the subsequently added phthalate coupling agent can be embedded between its layers, thereby effectively widening the interlayer spacing of nanographene oxide, which is conducive to being easily peeled off again to form a single-layer structure during the subsequent regeneration process.
[0021] Furthermore, the nano-graphene oxide is selected from nano-graphene oxide with a D50 of 80-85 nm and a particle size distribution range of 60-100 nm.
[0022] By selecting nano-graphene oxide with a suitable particle size and a relatively concentrated particle size distribution range, it is easier to disperse evenly in the system, thereby avoiding the situation where the local graphene oxide force in different parts is different from that in other areas, resulting in inconsistent PE crystallization behavior in different areas, insufficient local aging resistance and overall failure.
[0023] Furthermore, the thermoplastic elastomer is selected from any one of styrene-based thermoplastic elastomer TPS, polyolefin-based thermoplastic elastomer TPV, polyamide-based thermoplastic elastomer TPAE or polyester-based thermoplastic elastomer TPEE.
[0024] Further, the cooling includes:
[0025] In a nitrogen atmosphere, the mixture was rapidly cooled to 80-85°C at a rate of 4-5°C / s, and then slowly cooled to room temperature at a rate of 0.5-0.8°C / s.
[0026] The crystallization process is regulated by a relatively fast cooling rate. Specifically, the faster cooling rate is easy to form smaller crystal nuclei, thereby improving the aging resistance of the product. However, after cooling to 80-85°C, the relatively slower cooling rate is adjusted to ensure that the crystallization position is more uniform, which is beneficial to the balance of the overall aging resistance and minimize the possibility of local failure.
[0027] Furthermore, the phthalate coupling agent is selected from any one of phthalate coupling agent KR-9S, phthalate coupling agent KR-12, phthalate coupling agent KR-TTS, phthalate coupling agent KR-238, phthalate coupling agent TMC-201, and phthalate coupling agent TMC-102.
[0028] A recycled PE plastic is prepared by the above preparation method. DETAILED DESCRIPTION
[0029] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0030] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0031] Example 1
[0032] The recycled PE plastics are graded and processed. Specifically, the recycled PE plastics are divided into four grades: first-grade high-quality PE plastics, such as beverage bottles, with an impurity content of ≤0.5% after treatment; second-grade medium-quality PE plastics, such as food packaging materials and secondary recycled materials, with an impurity content of 0.5% < ≤2.5% after treatment; third-grade low-quality PE plastics, such as agricultural mulch and papermaking waste, with an impurity content of 2.5% < ≤10% after treatment; fourth-grade inferior PE plastics, with an impurity content of >10%; first-grade high-quality PE plastics are selected as raw materials;
[0033] After soaking the first-grade high-quality PE plastic in water for 1 hour, the plastic is repeatedly rinsed and washed for 3 times, and dried to remove moisture, so as to obtain a pretreated first-grade high-quality PE plastic;
[0034] The nano-graphene oxide and water were mixed in a mass ratio of 1:7, and ultrasonically dispersed for 40 minutes at an ultrasonic frequency of 180 kHz, and then the pH was adjusted to 7.4, and then a phthalate coupling agent of 6% of the mass of the nano-graphene oxide was added, and after heating and stirring for reaction, the mixture was filtered, washed and dried to obtain the modified nano-graphene oxide;
[0035] The nano graphene oxide is selected from nano graphene oxide with a D50 of 80 nm and a particle size distribution range of 60-100 nm;
[0036] The phthalate coupling agent is selected from phthalate coupling agent KR-9S;
[0037] The pretreated first-grade high-quality PE plastic, modified nano-graphene oxide and thermoplastic elastomer are heated to 160° C. in a mass ratio of 95:6:10, and are kept in an inert gas protection state and low-speed shear mixed for 8 hours at a shear rate of 80 r / min, and then extruded and granulated. In a nitrogen atmosphere, the plastic is rapidly cooled to 80° C. at a rate of 4° C. / s, and then slowly cooled to room temperature at a rate of 0.5° C. / s to obtain a recycled PE plastic;
[0038] The thermoplastic elastomer is selected from styrene thermoplastic elastomer TPS.
[0039] Example 2
[0040] The recycled PE plastics are graded and processed. Specifically, the recycled PE plastics are divided into four grades: first-grade high-quality PE plastics, such as beverage bottles, with an impurity content of ≤0.5% after treatment; second-grade medium-quality PE plastics, such as food packaging materials and secondary recycled materials, with an impurity content of 0.5% < ≤2.5% after treatment; third-grade low-quality PE plastics, such as agricultural mulch and papermaking waste, with an impurity content of 2.5% < ≤10% after treatment; fourth-grade inferior PE plastics, with an impurity content of >10%; first-grade high-quality PE plastics are selected as raw materials;
[0041] After soaking the first-grade high-quality PE plastic in water for 1 hour, the plastic is repeatedly rinsed and washed for 3 times, and dried to remove moisture, so as to obtain a pretreated first-grade high-quality PE plastic;
[0042] The nano-graphene oxide and water were mixed in a mass ratio of 1:7, and ultrasonically dispersed for 50 minutes at an ultrasonic frequency of 190 kHz, and then the pH was adjusted to 7.5, and then a phthalate coupling agent of 7% of the mass of the nano-graphene oxide was added, and after heating and stirring for reaction, the mixture was filtered, washed and dried to obtain the modified nano-graphene oxide;
[0043] The nano graphene oxide is selected from nano graphene oxide with a D50 of 82nm and a particle size distribution range of 60-100nm;
[0044] The phthalate coupling agent is selected from phthalate coupling agent KR-12;
[0045] The pretreated first-grade high-quality PE plastic, modified nano-graphene oxide and thermoplastic elastomer are heated to 162° C. in a mass ratio of 98:7:11, and are kept warm and low-speed shear mixed for 10 hours at a shear rate of 100 r / min under an inert gas protection state, extruded and granulated, and rapidly cooled to 82° C. at a rate of 4.5° C. / s in a nitrogen atmosphere, and then slowly cooled to room temperature at a rate of 0.6° C. / s to obtain recycled PE plastic;
[0046] The thermoplastic elastomer is selected from polyolefin thermoplastic elastomer TPV.
[0047] Example 3
[0048] The recycled PE plastics are graded and processed. Specifically, the recycled PE plastics are divided into four grades: first-grade high-quality PE plastics, such as beverage bottles, with an impurity content of ≤0.5% after treatment; second-grade medium-quality PE plastics, such as food packaging materials and secondary recycled materials, with an impurity content of 0.5% < ≤2.5% after treatment; third-grade low-quality PE plastics, such as agricultural mulch and papermaking waste, with an impurity content of 2.5% < ≤10% after treatment; fourth-grade inferior PE plastics, with an impurity content of >10%; first-grade high-quality PE plastics are selected as raw materials;
[0049] After soaking the first-grade high-quality PE plastic in water for 1 hour, the plastic is repeatedly rinsed and washed for 3 times, and dried to remove moisture, so as to obtain a pretreated first-grade high-quality PE plastic;
[0050] The nano-graphene oxide and water were mixed in a mass ratio of 1:7, and ultrasonically dispersed for 60 minutes at an ultrasonic frequency of 200 kHz, and then the pH was adjusted to 7.6, and then a phthalate coupling agent of 8% of the mass of the nano-graphene oxide was added, and after heating and stirring for reaction, the mixture was filtered, washed and dried to obtain the modified nano-graphene oxide;
[0051] The nano graphene oxide is selected from nano graphene oxide with a D50 of 85 nm and a particle size distribution range of 60-100 nm;
[0052] The phthalate coupling agent is selected from phthalate coupling agent KR-TTS;
[0053] The pretreated first-grade high-quality PE plastic, modified nano-graphene oxide and thermoplastic elastomer are heated to 165° C. in a mass ratio of 100:8:12, and are kept warm and low-speed shear mixed for 12 hours at a shear rate of 120 r / min under an inert gas protection state, extruded and granulated, and rapidly cooled to 85° C. at a rate of 5° C. / s in a nitrogen atmosphere, and then slowly cooled to room temperature at a rate of 0.8° C. / s to obtain recycled PE plastic;
[0054] The thermoplastic elastomer is selected from polyamide thermoplastic elastomer TPAE.
[0055] Example 4
[0056] Compared with Example 1, this embodiment is different in that:
[0057] The pretreated first-grade high-quality PE plastic, modified nano-graphene oxide and thermoplastic elastomer are heated to 160° C. in a mass ratio of 95:6:10, and are kept under low-speed shear mixing for 8 hours at a shear rate of 80 r / min under inert gas protection, extruded and granulated, and rapidly cooled to room temperature at a rate of 4° C. / s in a nitrogen atmosphere to obtain recycled PE plastic;
[0058] The rest of the conditions remain unchanged.
[0059] Example 5
[0060] Compared with Example 1, this embodiment is different in that:
[0061] The pretreated first-grade high-quality PE plastic, modified nano-graphene oxide and thermoplastic elastomer are heated to 160° C. in a mass ratio of 95:6:10, and are kept warm and low-speed shear mixed for 8 hours at a shear rate of 80 r / min under inert gas protection, extruded and granulated, and slowly cooled to room temperature at a rate of 0.5° C. / s in a nitrogen atmosphere to obtain recycled PE plastic.
[0062] Comparative Example 1
[0063] Compared with Example 1, this comparative example has the following differences:
[0064] No phthalate coupling agent was added, and the other conditions remained unchanged.
[0065] Comparative Example 2
[0066] The difference between this comparative example and Example 1 is that no modified nano-graphene oxide is added, and the other conditions remain unchanged.
[0067] Comparative Example 3
[0068] The difference between this comparative example and Example 1 is that no thermoplastic elastomer is added, and other conditions remain unchanged.
[0069] The performance tests were performed on the products obtained in the examples and comparative examples. The specific test methods and test results are as follows:
[0070] The density is 1.2g / cm 3 Hollow silica particles are used as fillers, and their D50 is 80 μm;
[0071] According to the mass ratio of recycled PE plastic to hollow silica particles of 9:1, the products obtained in the above examples and comparative examples were mixed with the hollow silica particles of the above specifications, and kneaded in a vacuum kneader at 150°C and 2000r / min for 5 minutes. After cooling, the hydraulic cold and hot press was heated to 180°C, and the kneaded materials were placed in the hot pressing metal template cavity and pressed at a pressure of 4MPa for 2 minutes. After the hot pressing was completed, the sample was cold pressed at room temperature and a pressure of 15MPa for 5 minutes to obtain a thermal insulation material;
[0072] Thermal insulation performance test: Tested according to GB / T10294-2008. The sample diameter is 12mm and the thickness is 2mm. The calculation formula of thermal conductivity is:
[0073] Thermal conductivity = α × cp ×ρ(1)
[0074] In formula (1): α is the thermal diffusion coefficient of the sample, cm 2 / s;c p is the specific heat of the sample, J / (kg·K); ρ is the density of the sample, g / cm 3 .
[0075] The detailed test results are shown in Table 1;
[0076] The thermal insulation materials prepared from the products of each embodiment or comparative example were placed at a temperature of 70° C. and a relative humidity of 75% for 56 days of constant temperature and humidity simulated aging, and then the thermal conductivity after aging was tested again according to the above standard. The detailed test results are shown in Table 1.
[0077] Table 1: Product performance test results
[0078]
[0079] It can be seen from the test results in Table 1 that when the product obtained by the present invention is prepared as a thermal insulation material, it has a relatively low thermal conductivity, can obtain a good thermal insulation effect, and can still maintain an excellent thermal insulation effect after a long period of wet heat aging simulation test.
[0080] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing recycled PE plastic, characterized in that: The specific preparation steps include: The recycled PE plastics are graded and first-class high-quality PE plastics are selected; The first-grade high-quality PE plastic is washed with water, and then dried to remove moisture to obtain a pretreated first-grade high-quality PE plastic; The pretreated first-grade high-quality PE plastic, modified nano-graphene oxide and thermoplastic elastomer are heated to 160-165° C. in a mass ratio of (95-100): (6-8): (10-12), and are kept warm and low-speed shear mixed for 8-12 hours under an inert gas protection state, and then extruded and granulated, and cooled to obtain recycled PE plastic; Phthalate coupling agents are embedded between the layers of the modified nano-graphene oxide.
2. The method for preparing recycled PE plastic according to claim 1, characterized in that: The heat preservation low speed shear mixing comprises: Low speed shear mixing is performed at a shear rate of 80-120 r / min.
3. The method for preparing recycled PE plastic according to claim 1, characterized in that: The first-grade high-quality PE plastic is selected from beverage bottles made of PE material.
4. The method for preparing recycled PE plastic according to claim 1, characterized in that: The specific modification steps of the modified nano graphene oxide include: After mixing nano graphene oxide and water, ultrasonically disperse them for 40-60 minutes under an ultrasonic frequency of 180-200kHz, adjust the pH to 7.4-7.6, add 6-8% of the mass of the nano graphene oxide phthalate coupling agent, heat and stir to react, filter, wash and dry to obtain modified nano graphene oxide.
5. The method for preparing recycled PE plastic according to claim 4, characterized in that: The nano graphene oxide is selected from nano graphene oxide with a D50 of 80-85 nm and a particle size distribution range of 60-100 nm.
6. The method for preparing recycled PE plastic according to claim 1, characterized in that: The thermoplastic elastomer is selected from any one of styrene-based thermoplastic elastomer TPS, polyolefin-based thermoplastic elastomer TPV, polyamide-based thermoplastic elastomer TPAE or polyester-based thermoplastic elastomer TPEE.
7. The method for preparing recycled PE plastic according to claim 1, characterized in that: The cooling comprises: In a nitrogen atmosphere, the mixture was rapidly cooled to 80-85°C at a rate of 4-5°C / s, and then slowly cooled to room temperature at a rate of 0.5-0.8°C / s.
8. The method for preparing recycled PE plastic according to claim 1, characterized in that: The phthalate coupling agent is selected from any one of phthalate coupling agent KR-9S, phthalate coupling agent KR-12, phthalate coupling agent KR-TTS, phthalate coupling agent KR-238, phthalate coupling agent TMC-201 and phthalate coupling agent TMC-102.
9. A recycled PE plastic, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Environment-friendly recycled plastic particles and preparation method thereof
CN108003430A
Preparation method of building heat-preservation thermal-insulation composite material
CN109279811A
Modified regenerated PE nano composite material and preparation method thereof
CN111234343A
